Cumulative deamidations of the major lens protein γS‐crystallin increase its aggregation during unfolding and oxidation. (28th August 2020) - Vetter, Calvin J.; Thorn, David C.; Wheeler, Samuel G.; Mundorff, Charlie C.; Halverson, Kate A.; Wales, Thomas E.; Shinde, Ujwal P.; Engen, John R.; David, Larry L.; Carver, John A.; Lampi, Kirsten J.
Abstract: Age‐related lens cataract is the major cause of blindness worldwide. The mechanisms whereby crystallins, the predominant lens proteins, assemble into large aggregates that scatter light within the lens, and cause cataract, are poorly understood. Due to the lack of protein turnover in the lens, crystallins are long‐lived. A major crystallin, γS, is heavily modified by deamidation, in particular at surface‐exposed N14, N76, and N143 to introduce negative charges. In this present study, deamidated γS was mimicked by mutation with aspartate at these sites and the effect on biophysical properties of γS was assessed via dynamic light scattering, chemical and thermal denaturation, hydrogen‐deuterium exchange, and susceptibility to disulfide cross‐linking. Compared with wild type γS, a small population of each deamidated mutant aggregated rapidly into large, light‐scattering species that contributed significantly to the total scattering. Under partially denaturing conditions in guanidine hydrochloride or elevated temperature, deamidation led to more rapid unfolding and aggregation and increased susceptibility to oxidation. The triple mutant was further destabilized, suggesting that the effects of deamidation were cumulative. Molecular dynamics simulations predicted that deamidation augments the conformational dynamics of γS. We suggest that these perturbations disrupt the native disulfide arrangement of γS and promote the formation of disulfide‐linked aggregates. The lens‐specific chaperone αA‐crystallin was poor at preventing the aggregation of the triple mutant. It is concluded that surface deamidations cause minimal structural disruption individually, but cumulatively they progressively destabilize γS‐crystallin leading to unfolding and aggregation, as occurs in aged and cataractous lenses.